Effective recovery of Ti as anatase nanoparticles from waste red mud via a coupled leaching and boiling route - Qu, Zhan; Liu, Jiancong; Su, Ting; Zhu, Suiyi; Liu, Junzhen; Chen, Yusen (Frontiers in Chemistry, 2023)
Red mud (RM) a solid waste generated by the bauxite smelting industry, is a rich source of metal resources, especially Ti, and its recycling can bring significant environmental and economic benefits. In this study, precious metal Ti was efficiently recovered from RM using a coupled acid leaching and boiling route for the effective separation of low-value metals. The RM which contained mainly 10.69% Si, 12.1% Al, 15.2% Ca, 10.99% Fe, and 4.37% Ti, was recovered in five steps. First, a nitric acid solution was used to leach the metals in multiple stages, resulting in an acidic leach solution with high concentrations of Fe, Al, Ti, and Ca ions 2.7 g/L, 4.7 g/L, 5.43 g/L, and 1.8 g/L, respectively. Then, a small amount of sucrose was added as a catalyst to recover Ti from the leach solution under hydrothermal conditions, resulting in the targeted recovery of 98.6% of Ti in the form of high-purity anatase while Fe, Al, and Ca remained in the solution. Next, a secondary hydrothermal approach was used to recover Fe and Al from the solution through extreme regulation of temperature, time, and pressure parameters, resulting in the production of two high-purity by-products, hematite and boehmite. Finally, the remaining Ca in solution was recovered by simple pH regulation. Economic accounting assessment showed that the method yields $101.06 for 1 t of RM treated, excluding labor costs. This study provides a novel approach to recover precious metals from metal wastes through the whole process resource recovery of solid waste RM.